2005
DOI: 10.1007/bf02898196
|View full text |Cite
|
Sign up to set email alerts
|

Different conditions of cold water immersion test for diagnosing hand-arm vibration syndrome

Abstract: The cold water immersion test with finger skin temperature (FST) measurement is used to assess vascular disorders in hand-arm vibration syndrome (HAVS). The test method is currently being standardized within the International Organization for Standardization (ISO) in which a water temperature of 12°C for 5 min of hand immersion and an option of using a waterproof hand covering during immersion are proposed. It is necessary to evaluate the diagnostic significance of the test with FST measurement under different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Because of environmental exposures and cold surroundings, it is difficult to avoid exposure to cold air; however, patients may avoid cold water immersion by substituting warmer water temperatures. Multiple studies of cold sensitivity and clinical evaluations of vascular disorders in the hand have used cold water immersion as a cold stimulus [8, 11, 24, 28]. In our cold chamber laboratory, we are able to control air temperature and humidity and have initiated an investigation to evaluate the responses with cold air exposure compared to cold water immersion as a cold stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Because of environmental exposures and cold surroundings, it is difficult to avoid exposure to cold air; however, patients may avoid cold water immersion by substituting warmer water temperatures. Multiple studies of cold sensitivity and clinical evaluations of vascular disorders in the hand have used cold water immersion as a cold stimulus [8, 11, 24, 28]. In our cold chamber laboratory, we are able to control air temperature and humidity and have initiated an investigation to evaluate the responses with cold air exposure compared to cold water immersion as a cold stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Ring [36] used a cooling time of 60 s in water temperature from 0 to 20°C for Raynaud's phenomenon. Laskar and Harada [40] proposed the cold water immersion test for diagnosing hand-arm vibration syndrome in temperature 10°C and 15°C in immersion time 1, 5, and 10 min. When the infrared measurement technique was applied to our population with our cold provocation test in water 0°C for 5 s, there was a tendency for the mean Tmax-Tmin temperatures to be lower by 4-5°C.…”
Section: Discussionmentioning
confidence: 99%
“…The sample battery was immersed in a water tank of 1 M, and the battery was observed for 30 minutes. However, it was confirmed that the protection circuit against flooding was operating normally because no fire or explosion occurred [15,16].…”
Section: Test Itemsmentioning
confidence: 97%